ISOLATION, CHARACTERIZATION AND MANAGEMENT OF PYTHIUM APHANIDERMATUM CAUSING SOFT ROT OF GINGER (Journal of Plant Disease Sciences, 2025)
Ginger (Zingiber officinale Rosc.), an important spice crop cultivated extensively in tropical and subtropical regions, is severely affected by soft rot disease caused by Pythium aphanidermatum. The present study was undertaken to isolate and identify the causal organism from infected ginger rhizomes collected from farmers’ fields and to evaluate the efficacy of different biocontrol agents against the pathogen under in vitro conditions. The pathogen was successfully isolated on potato dextrose agar (PDA) and identified based on its cultural and microscopic characteristics. Pathogenicity of P. aphanidermatum was confirmed using rhizome inoculation methods, including rhizome dip, rhizome injection and soil inoculation techniques. Eight biocontrol agents comprising six fungal agents, namely Trichoderma asperellum, Trichoderma harzianum, Trichoderma virens, Aspergillus niger, Metarhizium anisopliae and Paecilomyces lilacinus, and two bacterial agents, Bacillus subtilis and Pseudomonas fluorescens, were evaluated against the pathogen using the dual culture technique. Among the tested biocontrol agents, Trichoderma asperellum was found to be the most effective, recording 70.36% inhibition of mycelial growth of P. aphanidermatum. The results indicate that fungal biocontrol agents, particularly Trichoderma asperellum, can serve as eco-friendly and sustainable alternatives to chemical fungicides for the management of soft rot disease of ginger.
Keywords: Biological control, Ginger, Pythium, Soft rot, Trichoderma